Preparation of High-Refractive-Index Flexible Nanoparticle Laser Engraving Materials and Micro-Nano Sculpture Art - Zhilei Guo; Liling Huang; Li Tian (Advances in Materials Science and Engineering)
The continuous development of nanotechnology has brought new trends of thought and new impetus to sculpture art. In the field of microengraving, people usually use two-photon engraving technology, but not every particle conforms to the engraving process. ZnO nanoparticles have a high refractive index and are extremely flexible, making them the material of choice for laser engraving. This article aims to investigate whether the incorporation of high-refractive-index flexible nanoparticles into engraving techniques can significantly improve the functional properties of products. This paper firstly introduces the preparation methods of common nanoparticle laser engraving materials and then describes simple micro-nano sculptures on this basis. Finally, experiments on the transmittance and refractive index of ZnO nanoparticles are carried out. The experimental results show that the refractive index and transmittance of this material are 1.7 and 1.039, respectively, which is very suitable for laser engraving.